FOXP1: a potential therapeutic target in cancer. - Koon, H; Ippolito, G; Banham, A; Tucker, P (2007)
Forkhead Box P1 (FOXP1) is a member of the FOX family of transcription factors which have a broad range of functions. Foxp1 is widely expressed and has been shown to have a role in cardiac, lung and lymphocyte development. FOXP1 is targeted by recurrent chromosome translocations and its overexpression confers a poor prognosis in a number of types of lymphomas, suggesting it may function as an oncogene. In contrast, FOXP1 localises to a tumour suppressor locus at 3p14.1 and loss of FOXP1 expression in breast cancer is associated with a worse outcome, suggesting FOXP1 may function as a tumour suppressor in other tissue types. These data suggest that FOXP1 may not only be useful in prognosis but also may be used to develop FOXP1-directed therapeutic strategies.